Peningkatan Kesadaran Ergonomi melalui Edukasi Postur Kerja bagi Pekerja Rumahan - Ikbal Anggara (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The increasing trend of working from home since the COVID-19 pandemic has introduced new occupational health challenges, particularly regarding ergonomics. This study aimed to improve ergonomic awareness through structured education on proper work postures for home-based workers. Using a one-group pretest-posttest design, the research evaluated the effectiveness of educational interventions based on behavior change theories. Results demonstrated that interventions using the Trans-Theoretical Model (TTM) reduced Rapid Office Strain Assessment (ROSA) scores from 5.65 to 3.95 and decreased forward head posture by 9°. Similarly, participatory ergonomic approaches increased straight back posture from 59% to 75% of work time, with a 98% participant satisfaction rate. Educational strategies combining short workplace demonstrations, reminder media, and physical exercises proved more effective than conventional training methods. Theory-based weekly training sessions reduced the proportion of high-risk workers from 60% to 21% within three months. The study concludes that structured work posture education based on behavior change theories effectively enhances ergonomic awareness among home-based workers and significantly reduces health risks associated with poor posture.